A Comparative Study of the Professional Competency Framework for Music Teachers in Thailand and the European Union - Thuntawech, Mintra; Boriboonviree, Natthawut (Journal of Education Studies, Chulalongkorn University, 2024)
The study of music teacher competency is a study of music teachers’ ability to integrate knowledge and skills in teaching and music, including appropriate behavior as a guideline for music teachers in their own work and professional development. The purpose of this research is to compare the competencies of music teachers in Thailand and the European Union by means of document research, comparing data between the Teachers Council regulations on professional standards and the announcement of the Ministry of Education on the standard framework for bachelor’s degree qualifications in the field of education and music education, and Report on the education of music teachers from the perspective of the European Union. The results of the study show that the music teacher competency frameworks of Thailand and the European Union, although they have different focuses and presentation methods according to the context of application in each country, are consistent in their key principles. The competencies of music teachers can be classified into 6 areas, consisting of 1) music knowledge and skills, 2) teaching and learning management, 3) communication and technology, 4) teaching and learning research, 5) relationships with individuals and communities and 6) ethics and conduct. Studying the competency framework for music teachers will be beneficial to the process of improving the production and development of music teachers in Thailand to be modern and consistent with the needs and changes in the social context.